Development of industrial air pollution monitoring system for safety and health enhancement and sustainable work environment in Small and Medium Industries (SMI's) / Abdul Mutalib Leman - Leman, Abdul Mutalib (2011)
The study is focused on the development of Industrial Air Pollution Monitoring System (IAPMOS) for small and medium industries application. The objectives of the study are to develop a system with special configuration on wireless datacommunications with the ability to analyze hazard and risk especially in welding process. The Quality Function Deployment (QFD) was used as a tool in the design of the system. Questionnaires were distributed to the relevant personnel in the related manufacturing industries. Case studies were carried out in two manufacturing companies located in Shah Alam, Selangor. Another case study on wireless data communication was conducted in the Walk-in Stability Chamber (WiSC) at Universiti Tun Hussein Onn Malaysia (UTHM). The system analyzed the data after save file and it is used as the Hazard Risk Index (HRI) approach. The results on risk level were used for Risk Classification Matrix (RCM) approach. The system features have warning signs (by colour) and buzzer to ensure the safety and health personnel paid attention to the outcome toxic gas data collected. The system can reach 150m lengthfor accurate wireless data transfer. The IAPMOS can be used by the industries to create safe, healthy and sustainable work environment and reduce occupational diseases.